2019
DOI: 10.31873/ijetr.9.4.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

“Illiteracy – A social Issue” A brief study in the Indian population

Abstract: Illiteracy is one of the biggest issues of the modern world; it is found in every corner of the world. And hence we are focusing the depth of this issue in our localities and peer groups. This article is a small-scale survey with data from 500 individual from around the country, asking few important questions to understand the reality of this issue and giving few solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to Bhatia 2013, several people among the poor cluster who are socially disadvantaged and the majority of people who are residing in the rural area than people in urban areas are equally illiterate and in this group, women are more illiterate than men, it is obvious that the low number of female literacy is a factor for their full dependency on men for writing and reading activities (Chaurasia, Priya & Agrawal, 2019). It has been established that the impacts of illiteracy on the life of concerned have always been negative when people cannot write, read or tackle a numerical problem they tend to confront with enormous problems such as inability to open a bank account, carry out online transactions or secure a good job, even if they are to get a job at all they can only get menial jobs such as domestic labour, carpentry, cleaning etc which cannot really sustain them for their livelihood (Chaurasia, Priya & Agrawal, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bhatia 2013, several people among the poor cluster who are socially disadvantaged and the majority of people who are residing in the rural area than people in urban areas are equally illiterate and in this group, women are more illiterate than men, it is obvious that the low number of female literacy is a factor for their full dependency on men for writing and reading activities (Chaurasia, Priya & Agrawal, 2019). It has been established that the impacts of illiteracy on the life of concerned have always been negative when people cannot write, read or tackle a numerical problem they tend to confront with enormous problems such as inability to open a bank account, carry out online transactions or secure a good job, even if they are to get a job at all they can only get menial jobs such as domestic labour, carpentry, cleaning etc which cannot really sustain them for their livelihood (Chaurasia, Priya & Agrawal, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The illiterates and poor people in that setting are suffered most to secure employment in such environment due to lack of skill to conduct themselves with the requirements of the job, in the long run, the lack sufficient food to take and lack proper nutrition. As result, they lack skills which make the be at disadvantage to secure good job (Chaurasia, Priya & Agrawal, 2019;Richmond, Robinson, Sachs-Israel & Sector, 2008). Past studies have shown that the Islamic finance market is recording growth with an approach aiming at human increase people`s income through assisting small and medium enterprise and human well-being (AbdulKareem, Mahmud, Abdulganiyy & Yazid; Irfan, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…According to Bhatia 2013, several people among the poor cluster who are socially disadvantaged and the majority of people who are residing in the rural area than people in urban areas are equally illiterate and in this group, women are more illiterate than men, it is obvious that the low number of female literacy is a factor for their full dependency on men for writing and reading activities (Chaurasia, Priya & Agrawal, 2019). It has been established that the impacts of illiteracy on the life of concerned have always been negative when people cannot write, read or tackle a numerical problem they tend to confront enormous problems such as the inability to open a bank account, carry out online transactions or secure a good job, even if they are to get a job at all they can only get menial jobs such as domestic labor, carpentry, cleaning, etc which cannot really sustain them for their livelihood (Chaurasia, Priya & Agrawal, 2019).…”
Section: Illiteracymentioning
confidence: 99%
“…The illiterates and poor people in that setting are suffered most to secure employment in such an environment due to lack of skill to conduct themselves with the requirements of the job, in the long run, the lack sufficient food to take and lack proper nutrition. As result, they lack skills which make them be at disadvantage to secure a good job (Chaurasia, Priya & Agrawal, 2019;Richmond, Robinson, Sachs-Israel & Sector, 2008). Past studies have shown that the Islamic finance market is recording growth with an approach aiming at human increase people`s income through assisting small and medium enterprise and human well-being (AbdulKareem, Mahmud, Abdulganiyy & Yazid; Irfan, 2020).…”
Section: Illiteracymentioning
confidence: 99%